PENGARUH PEMBUATAN MODUL BERBASIS WEBSITE TERHADAP PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR - Wahyuni Fajar Arum; Sutini (Jurnal Genta Mulia, 2024)
This research aims to determine the effect of fluid practicum by creating website-based modules on learning motivation and conceptual understanding of students in the Science Education Study Program, Faculty of Tarbiyah and Teacher Training, Sunan Ampel State Islamic University, Surabaya. The sample in this research was 60 students of the Science Education Study Program. The sampling technique uses non-probability sampling, namely purposive sampling. The research instruments used were observation, documentation and tests. The results of the T-test on learning motivation scores obtained a t-table value of 1.70113 while the t count was 41.573. From these results it can be concluded that the t table value < t calculated so that H0 is rejected, then there is an influence of fluid practicum activities by creating website-based modules on student learning motivation. The T test results from the pretest and posttest values obtained a t-table value of 1.70113 while the tcount was 48.612. From these results it can be concluded that the t table value < t calculated so that H0 is rejected, then there is an influence of fluid practicum activities by creating website-based modules on student understanding.